Surat Al-Lahab Dalam Studi Analisis Stilistika - Zakia Fikriyah Rahman (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2020)
Alquran as a holy book that full of aesthetic elements, needs to be proven with a linguistic approach. Stylistics, one of the linguistic approaches, is able to explain the relationship of language with its artistic function and meaning, as well as showing the use of language in a text, especially in the phenomenon of deviation and language preferences, in order to obtain special effects and certain meanings. Surah al-Lahab is the material object in this paper and stylistics is the formal object. Surah al-Lahab was chosen in this study because it contains a unique and interesting language style to be discussed and studied from the perspective of stylistics, both in aspects of phonology, morphology, syntax, semantics and imagery. This research is a type of qualitative research. This paper aims to identify and describe aspects in stylistic studies in order to get a perfect understanding of surah al-Lahab. The results of this study are 1) surat al-Lahab has aesthetics of perfect linguistic style, both from sounds, words and sentences, 2) the selection of flosive consonant sounds that are more than the fricative sounds, conforms to the meaning contained in this letter, 3) according to the morphological, syntactic, and semantic aspects, it is found that there are deviations or preferences in the form of words, words or sentences that make surah al-Lahab has its own special meaning, 4) Surat al-Lahab contains the building elements of beauty, namely majâz and jinâs.